Lesson Study Through the Project-Based Learning Model to Improve Creative Thinking Ability - Pratiwi, Rani Tania; Rismawati, Rismawati; Nuryatin, Atin; Rosaline, Caecilia Dina; Suryani, Yeyen; Agustira, Deden (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Thinking creatively is crucial for students' academic and personal development. This study aims to analyze the impact of the Lesson Study-based Project-Based Learning (PjBL) model on the creative thinking skills of seventh-grade students in social studies at SMP Negeri 2 Cimahi. The research was motivated by students' low creative thinking ability, as indicated by their reliance on textbooks and lack of initiative in independent problem-solving. This study employed a quasi-experimental method with a non-equivalent control group design, involving two groups: an experimental group that received Lesson Study-based PjBL and a control group taught using the lecture method. Data were collected through pre-tests and post-tests, classroom observations, and documentation. The data analysis used quantitative statistical techniques to compare the improvement in students' creative thinking abilities. The results revealed a significant difference between the two groups, with the experimental group showing a higher increase in creative thinking skills, particularly in fluency, flexibility, originality, and elaboration. These findings suggest that the Lesson Study-based PJBL model is an effective instructional approach to foster student creativity. Future research should explore its long-term impact and potential application in other subjects and educational levels.